Legal Analysis of Corporations with Alleged Exploitation of 1,047 Indonesian Students by Corporations in Internship Programs in Germany - Maharani, Riefda Nardi; Aulia, Azkia Nur; Athallah, Muhammad Nail; Haritsah, Ananda Rafli; Gultom, Jasmine Dameria; Raymma, Aracely (Rechtsvinding, 2025)
Trafficking in persons is the act of recruiting, transporting, harboring, sending, transferring, or receiving a person by threat of violence, use of force, abduction, harboring, falsification, deception, abuse of power or vulnerable position, debt bondage or giving payments or benefits, so as to obtain the consent of the person who has control over the other person, both within the country and between countries, for the purpose of exploitation or resulting in exploitation. The practice of transnational crimes of trafficking in persons that violate human dignity has been going on throughout history in various parts of the world, including in Indonesia. This deep-rooted global phenomenon is essentially a modern manifestation of slavery, which fundamentally deprives people of their fundamental rights. This research uses a normative juridical method to analyze and examine the legal review related to the Crime of Trafficking in Persons in the case of exploitation of Indonesian students to Germany, legal responsibility for TPPO perpetrators, and countermeasures in the criminal justice system. The results show that international organizations such as IOM are needed to prevent similar cases in the future. The governments of Indonesia and Germany, together with international institutions, must improve regulations, supervision, and strict sanctions to prevent the occurrence of TPPO cases.